Higher Viral Load of Emerging Norovirus GII.P16-GII.2 than Pandemic GII.4 and Epidemic GII.17, Hong Kong, China - Cheung, Sarah K.C. (Emerg Infect Dis, 2019)
We compared viral load of emerging recombinant norovirus GII.P16-GII.2 with those for pandemic GII.Pe-GII.4 and epidemic GII.P17-GII.17 genotypes among inpatients in Hong Kong. Viral load of GII.P16-GII.2 was higher than those for other genotypes in different age groups. GII.P16-GII.2 is as replication competent as the pandemic genotype, explaining its high transmissibility and widespread circulation.